If You Believe, It May Come True: The Relationship and Mechanism Between Self-Occupation Stereotypes of Private Kindergarten Teachers and Their Turnover Intention in China-Mainland - Yang, Feng; Han, Yang; Li, Minyan (Frontiers in Psychology, 2021)
In China-Mainland, the turnover rate of private kindergarten teachers remains high for a long time. With 692 Chinese private kindergarten teachers as subjects, we applied a questionnaire survey to examine the relationship between self-occupation stereotypes held by private kindergarten teachers and their turnover intention and the underlying mechanisms. The structured equation model (SCM) was conducted to analyse data and revealed a significantly positive correlation between self-occupation stereotypes and turnover intention. Further analyses showed that on the individual level, personal control sense mediated the relationship between self-occupation stereotypes and turnover intention, and on the organization level, professional identity mediated the relationship between them. Additionally, self-occupation stereotypes were also related to turnover intention via the chain-mediating role of personal control sense and professional identity. The current research firstly clarified the acting paths between self-occupation stereotypes of private kindergarten teachers and turnover intention on both the individual and the organization levels. In practice, the research provided a novel perspective for policy makers to alleviate the turnover tendency of private kindergarten teachers.